Number of participants in multiple perpetrator sexual aggressions - Giménez-Salinas Framis, Andrea (Legal and criminological psychology, 2023)
The present study aims to explore differences between lone, duo and 3+ group sexual aggressions by adult strangers from a Spanish sample based on victims' and offenders' socio-demographic characteristics and sexual offences. Additionally, the study aims to provide evidence of whether duo offences should be considered a different category that MPR and whether we can differentiate them from lone and 3+ group offenders. A sample of 400 sexual stranger offenders whose victims were women over 13 years of age has been analysed to find differences and predictive variables for lone (N = 298), duo (N = 43) and 3+ group (N = 59) sexual aggressions. Kruskal–Wallis tests and chi-squared analysis were used to compare the three groups and then multinomial logistic regression analysis were conducted to identify the predictive variables of group size. Results support previous studies comparing group sexual offences by its size; and that duos could be a singular category with more similarities with multiple perpetrator rape offences (age and ethnicity of offenders, similar violent control and sexual behaviour during the aggression). Some singularities have also been encountered, such as higher levels of alcohol and drug use of the perpetrators; severe consequences of their actions with more injuries to their victims; use of weapons; and less use of vehicles, which can be related to crime locations that are rarely outdoors.